2021
DOI: 10.1073/pnas.2026654118
|View full text |Cite
|
Sign up to set email alerts
|

Fe-catalyzed sulfide oxidation in hydrothermal plumes is a source of reactive oxygen species to the ocean

Abstract: Historically, the production of reactive oxygen species (ROS) in the ocean has been attributed to photochemical and biochemical reactions. However, hydrothermal vents emit globally significant inventories of reduced Fe and S species that should react rapidly with oxygen in bottom water and serve as a heretofore unmeasured source of ROS. Here, we show that the Fe-catalyzed oxidation of reduced sulfur species in hydrothermal vent plumes in the deep oceans supported the abiotic formation of ROS at concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In the long-term fertilized soils, H 2 O 2 and HO • increased slightly ( p > 0.05, except for HO • and total Fe) with total Fe and Fe­(II) (Figure S3). The correlation is weak because other soil components (e.g., SOM and minerals) affect the Fenton oxidation. ,, The SOM and minerals were removed in DNA-SIP microcosm experiments, leading to a very strong positive correlation between HO • and total Fe and Fe­(II) (Figure S6). Together, both long-term fertilization and DNA-SIP microcosm experiments indicated that HO • formation is derived from total Fe and Fe­(II) oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the long-term fertilized soils, H 2 O 2 and HO • increased slightly ( p > 0.05, except for HO • and total Fe) with total Fe and Fe­(II) (Figure S3). The correlation is weak because other soil components (e.g., SOM and minerals) affect the Fenton oxidation. ,, The SOM and minerals were removed in DNA-SIP microcosm experiments, leading to a very strong positive correlation between HO • and total Fe and Fe­(II) (Figure S6). Together, both long-term fertilization and DNA-SIP microcosm experiments indicated that HO • formation is derived from total Fe and Fe­(II) oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest obstacle is the complexity of soil components (including large amounts of free radical scavengers), hindering the direct measurement of hydroxyl radicals in soils . For instance, the reaction rate constants for HO • with DOC, CO 3 2– , and Fe 2+ are ∼1.8 to 8.4 × 10 8 , 3.7 × 10 8 , and 3.5 × 10 8 M –1 s –1 , respectively . In addition, abundant redox-active minerals in soils can be a sink or a source of HO • , challenging the HO • analyses .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breier et al 34 found that reduced and oxidized phases coexist in particle aggregates typically supported an organic matrix. Thus, the presence of a small amount of Fe(III) oxides does not imply that Fe sulfides have been completely removed or oxidized, but their co-occurrence in a sample within ∼1 m of the source does suggest rapid oxidation of soluble Fe(II), as found by Shaw et al 33 The slow reaction of these Fe(III) oxides with sulfide at the lower temperatures observed higher in the plume allows for their detection. Hoffman et al 35 reported common morphology and mineralogy of hydrothermally derived particulate Fe at sites 800−4300 km from the vent source, finding it present as aggregated Fe oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 86%
“…Short half-lives for Fe­(II) have been observed at other hydrothermal vent systems (<1 min, Mid Atlantic Ridge). Shaw et al showed that the reaction of Fe­(II) from vent waters with O 2 from bottom seawater led to H 2 O 2 but did not lead to soluble Fe­(III); thus, it is plausible that some Fe­(II) is oxidized and retained in the plume as Fe oxide nanoparticles. Breier et al found that reduced and oxidized phases coexist in particle aggregates typically supported by an organic matrix.…”
Section: Discussionmentioning
confidence: 99%